The creation of public value from the action of hybrid organisations (European journal of volunteering and community-based projects, 2021)
Increasingly, organisations occupy an intermediate position between public and private ownership;such organisations are called hybrid organisations (Doherty et al., 2014), whose goal is to createinnovation and synergy in addressing complex social issues, leading to more sustainabledevelopment (Karré, 2020).In the paper, we investigate how the actions of hybrid organisations produce public value, adoptinga conceptual scheme that relates broad strategic objectives of general (and public) interest to thepolicies that public administrations put in place.The objective is to plan and report on the sustainability and social impact dimensions of hybridorganisations, information that is central to the public sector entity, whose principal and specificrole is to provide quality services to the target community. The hybrid organisation must accountfor its social performance, report on it and draw up an action plan to improve its performance.Therefore, it is a process through which public administration can better understand the impact ofits actions on the community and, consequently, be accountable to its primary stakeholders.In this paper, we address the research question of how value creation is accounted for in hybridorganisations.Several approaches for reviewing the scientific stream can be applied in the management sector. Forexample, bibliometric reviews use a qualiquantitative approach to evaluate and monitor publishedresearch, considering statistics on authors, journals and countries (Zupic & Čater, 2015).According to Massaro et al., (2016), in bibliographic and bibliometric analysis, researchers may beinterested in representing a static picture, providing answers about the history of the research fieldunder investigation, and using bibliographic pairing of authors, keywords and citations.In our analysis, the composition of the research field was set: only products from the subject area'Business, Management & Accounting'. Following the studies by Mariani & Borghi, (2019),Massaro et al., (2016) and Secinaro et al., (2020), only "articles" written in the "English" languagewere considered. Following studies Li et al., 2017; Xu et al., (2018), articles published in journalson the ABS list (2018) with the classification at 1, 2, 3, 4 and 4* were considered. This choice iswidely adopted in bibliometric studies, and researchers commonly employ it to identify qualityscientific articles. We have also carefully reviewed the selected papers, highlighting those aspectsthat are useful for research and considering only those papers that have been published in journalsin the relevant subject area.To perform the biometric analysis, we used the Bibliometrix application: a statistical packageavailable on R-Studio (Aria & Cuccurullo, 2017); the software allows the representation ofbibliometric information, including authors, citations, countries of production and keywords andStructured literature review.